Syncope And Atrial Fibrillation: Which Is The Chicken And Which Is The Egg? - Hussain, Sara (J Atr Fibrillation, 2015)
Syncope and atrial fibrillation are both common entities and frequently occur together in an acute clinical scenario. Treatment of each in this presentation requires acquiring a good history and understanding the presentation of the patient. In this manuscript, there are 5 case studies that demonstrate common misperceptions when attempting to treat syncope when it presents with the arrhythmia atrial fibrillation. Rarely, does atrial fibrillation cause syncope. However, when a patient presents in atrial fibrillation, it becomes the focus of therapy rather than trying to define the etiology of the syncopal episode. It may be that well thought out algorithms to treat atrial fibrillation in an acute setting are replacing deductive thinking particularly when it comes to diagnosing the cause of a syncopal spell.